Relationship Between TNF-α and the Risk of Cerebral Palsy: A Systematic Review and Meta-Analysis - Wang, Baotian; Wang, Fan; Wu, De; Xu, Xiaoyan; Yang, Li; Zhu, Jing; Yuan, Jinjing; Tang, Jiulai (Frontiers in Neurology, 2022)
Objective: We performed a meta-analysis to investigate the relationship between blood tumour necrosis factor-alpha (TNF-α) levels and the risk of cerebral palsy (CP) in children. Methods: PubMed, Web of Science, Cochrane Library and Ovid databases were searched from the date of database inception to 26 April 2022. Data were extracted and pooled from observational studies related to TNF-α and the risk of CP in children. Quality was assessed using the Newcastle-Ottawa Scale. We used the inverse variance method with a random-effects model to estimate the odds ratios with 95% confidence intervals (CIs), and stratified analyses and sensitivity analysis were utilized to analyse heterogeneity. Results: Nine studies with 1117 cases and 3563 controls were included in our meta-analysis. The quality of the literature was good, and no publication bias was noted. According to the random-effects model, blood TNF-α levels were associated with the risk of CP (OR 1.82; 95% CI, 1.25-2.66) in a heterogeneous set of studies (I2=81.2%, p=0.000). Conclusion: Our findings indicate that elevated TNF-α levels in the blood are associated with an increased risk of CP. The association of TNF-α with CP requires further investigation.